Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Cumulative Review - Page 565: 42



Work Step by Step

$\frac{2x^{2}-50}{4x^{4}-20x^{3}}$ =$\frac{2(x^{2}-25)}{4x^{3}(x-5)}$ =$\frac{2(x^{2}-5^{2})}{4x^{3}(x-5)}$ =$\frac{2(x+5)(x-5)}{4x^{3}(x-5)}$ =$\frac{2(x+5)}{4x^{3}}$ =$\frac{(x+5)}{2x^{3}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.